Dual regulation of miR-375 and CREM genes in pancreatic beta cells. Issue 1 (31st December 2022) - Keller, David M.; Perez, Isis G.
ABSTRACT: MicroRNA-375 (miR-375) is upregulated in the islets of some diabetics and is correlated with poor outcome. Previous work in our laboratory showed that cyclic adenosine monophosphate (cAMP) reduces miR-375 expression and could provide a way to restore normal miR-375 levels, however the transcription repression mechanism is unknown. Using a chromatin immunoprecipitation assay we show that cAMP response element modulator (CREM) binds to the miR-375 promoter 3-fold above background and we find that CREM represses transcription from the miR-375 promoter 1.8-fold. While investigating miR-375 target genes we discovered that several microRNA:mRNA target prediction algorithms listed human CREM as a target gene of miR-375. The predicted binding site is conserved in primates but not in other species. We found that indeed miR-375 binds to the predicted site on human CREM and represses translation of a green fluorescent protein reporter gene by 30%. These findings suggest a primate-specific double-negative feedback loop, a mechanism that would keep these important β-cell regulators in check. Graphical Abstract: uf0001